2014
DOI: 10.3103/s1068799814010073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating on the load-carrying structure mass

Abstract: The effect of heating on the mass of load-carrying structures is analyzed using the weight Komarov formula in the framework of the design calculations by examples of a panel and spar. The results obtained have been compared with the data on real structures of supersonic passenger aircraft and aerospace aircraft of reusable transport systems.Weight is a major factor in aircraft design as well as one of the main criteria being used. The structure, which takes all spectrum of acting loads, accounts for the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…16 Previous studies have shown that beyond Mach 3 mission block time is not significantly reduced, 17 and thermal heating presents increasing difficulties despite advances in technology. 18 Once an engine is selected for the aircraft, the speed where it is most efficient, based on range gained per unit of fuel used, will be chosen as the final cruise speed for the ESPA.…”
Section: Executive Supersonic Passenger Aircraftmentioning
confidence: 99%
“…16 Previous studies have shown that beyond Mach 3 mission block time is not significantly reduced, 17 and thermal heating presents increasing difficulties despite advances in technology. 18 Once an engine is selected for the aircraft, the speed where it is most efficient, based on range gained per unit of fuel used, will be chosen as the final cruise speed for the ESPA.…”
Section: Executive Supersonic Passenger Aircraftmentioning
confidence: 99%
“…9 However, the penetration of smaller supersonic transports opens a niche to the hegemony of subsonic passenger aircraft. 3,5,8 This niche is spawning renewed research, particular into methodologies for design like multidisciplinary optimization, 1116 sonic boom minimization, 1719 aerothermal heating, 20 carbon emissions 8 and numerical augmentation of supersonic wind tunnel testing. 21…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, aerothermal heating is also an issue as Mach number increases. 20 Size in supersonic jets is limited because ‘ the strength of the shock waves generated by an aircraft flying at supersonic speed is a direct function of both the aircraft’s weight and its occupying volume ’. 23 For the Concorde and Tu-144 aircraft, the overpressure on the ground was around 110 and 120 Pa, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation